Microbial Diversity in Milk of Women With Mastitis: Potential Role of Coagulase-Negative Staphylococci, Viridans Group Streptococci, and Corynebacteria. (May 2017) - Mediano, Pilar; Fernández, Leonides; Jiménez, Esther; Arroyo, Rebeca; Espinosa-Martos, Irene; Rodríguez, Juan M.; Marín, María
Background: Lactational mastitis constitutes a significant cause of premature weaning. However, its etiology, linked to the presence of pathogenic microorganisms, has been scarcely reported. Research aim: The aim of this study was to describe the microbial diversity in milk samples from women suffering from lactational mastitis and to identify more accurately a collection of isolates belonging to coagulase-negative staphylococci, streptococci, and coryneform bacteria. Methods: This is a cross-sectional descriptive one-group study. A total of 5, 009 isolates from 1, 849 mastitis milk samples was identified by culture, biochemical, and/or molecular methods at the species or genus level. A more precise identification of a collection of 211 isolates was carried out by 16S rRNA gene sequencing. Results: Mean total bacterial count in milk samples was 4.11 log10 colony-forming units/ml, 95% confidence interval [4.08, 4.15]. Staphylococcus epidermidis was the most common species being isolated from 91.56% of the samples, whereas Staphylococcus aureus was detected in 29.74%. Streptococci and corynebacteria constituted the second (70.20%) and third (16.60%) most prevalent bacterial groups, respectively, found in this study. In contrast, Candida spp. was present in only 0.54% of the samples. Sequencing of the 16S rRNA gene revealed a high diversity of bacterial species among identified isolates. Conclusion: Many coagulase-negative staphylococci, viridans group streptococci, and corynebacteria, usually dismissed as contaminant bacteria, may play an important role as etiologic agents of mastitis. Proper diagnosis of mastitis should be established after performing microbiological testing of milk based on standardized procedures. A reliable analysis must identify the mastitis-causing pathogen(s) at the species level and its(their) concentration(s).